Therapeutic adherence in adults with type 2 diabetes in a chronic disease program. Huánuco 2017 - Acuña-Carbajal, Giannina (2019)
Objective: To assess whether knowledge about Diabetes Mellitus (DM), family functionality and depression are associated with Therapeutic Adherence in adults with type 2 DM. Methods: Analytical study of cross section. It was carried out in the diabetes program of CAP-UNHEVAL of Hospital II Essalud. Participants: patients with type 2 DM. Interventions: According to the inclusion and exclusion criteria. Validated collection instruments were used, interviewed for two months. The descriptive analysis was carried out; for inferential analysis: Chi2 test with 95% significance. The statistical package SPSS and Microsoft Excel was used. Results. The average age: 61.95 years, most frequent diseases: dyslipidemia (23.8%) and hypertension (43.6%). Knowledge about DM2 was not acceptable (86%), 95.9% with poor family function and 90.2% with depression were obtained. Variables associated with poor adherence to diabetic treatment were: family dysfunction [p = 0.00; RP = 26.18; CI: 95% (8.71 - 78.64)], unacceptable knowledge on DM2 [p = 0.00; RP= 23.57; 95% CI (8.54-65.06)] and depression [p = 0.00; RP= 6.81; 95% CI (3.00 - 15.45)]. Conclusions: Poor adherence to treatment is influenced by family dysfunction, poor knowledge about diabetes and depression.